Infrastructure as an indicator and subject of assessment in global, industry and specialized ratings - Olena Otych (Unìversiteti ì lìderstvo, 2024)
Based on the identification of the importance of the influence of infrastructure on the success of activities and the processes it provides, the article substantiates the feasibility of using it as an indicator for determining innovation potential, as well as a subject of assessment in infrastructure ratings. It is emphasized the need to study these ratings as bases of empirical data representing the importance and role of infrastructure in the innovative development of universities as centers around which innovative ecosystems should be built, which will act as drivers of the development of higher education, modernization of economic sectors, recovery and innovative progress of Ukraine after the end of the war. Global and industry ratings were analyzed, the indicators of which define infrastructure or activities related to its formation and development. The leading infrastructure rankings are characterized, in particular: THE Impact Rankings: Industry, Innovation and Infrastructure; Information and communication technologies and University–industry Research&Development collaboration as sub-ratings of WIPO The Global Innovation Index. The indicators used in these ratings as a basis for assessing the level of infrastructure development and its impact on the innovation potential of institutions, cities/regions and countries have been identified. A comparative analysis of the composition of top universities, which became the leaders of global and industry ratings, was carried out, the indicators of which are infrastructure. The place of the Ukrainian universities in these ratings in 2023 and 2024 by group was identified, the positive quantitative and qualitative dynamics of the representation of national higher education institutions and its dependence on the level of development of their innovative infrastructure were proven. Recommendations on the adaptation of the leading foreign experience in the development of the innovative infrastructure of universities in Ukraine in the conditions of post-war recovery have been formulated.